Empagliflozin improves prognosis and energetic properties through modulating mitochondrial function in failing murine hearts. (14th October 2021) - Shiraki, A; Oyama, J; Shimizu, T; Nakajima, T; Yokota, T; Node, K
Abstract: Background/Introduction: Sodium-glucose cotransporter 2 (SGLT2) inhibitors have been reported to have beneficial effects on heart failure in large clinical trials; however, the underlying mechanism is still unclear. Purpose: The purpose of this study is to elucidate the mechanism of cardioprotective effect of empagliflozin in heart failure. Methods: Eight-week-old mice deficient in cardiac and skeletal muscle-specific manganese superoxide dismutase, a mouse model of dilated cardiomyopathy (MnSOD-cKO mice), were given food mixed with or without 10 mg/kg empagliflozin for seven weeks and evaluated. Mitochondrial function in the cardiac muscle were measured by a high-resolution respirometer, Oxygraph-2K. Respiratory gas analysis were performed by indirect calorimetry (ARCO 2000) to estimate the energy consumption and energetic substrates. Results: The survival rate (P=0.015) and cardiac fibrosis (P=0.036) were significantly improved in the empagliflozin group. The capacity of oxidative phosphorylation in cardiac mitochondria was significantly improved by empagliflozin. Blood lactate levels were decreased in the empagliflozin group, indicating that energy such as ATP could be produced without resorting to anaerobic metabolism. Respiratory gas analysis revealed significant improvement in energy expenditure along with increase in food intake. Respiratory quotient was not different between the two groups, showing the consumption of the carbohydrate to fat rate was not changed by empagliflozin in this study. Ketone levels in blood and HbA1c were neither significantly different between the two groups. Although a moderate amount glucose was excreted in urine in the empagliflozin group (128.3±20.4 mg/day, 0.51±0.08 kcal/day), the available energy substrates in the whole body nonetheless expanded because of the increased caloric intake (10.58±0.72 in control group vs. 13.55±0.08 kcal/day in empagliflozin group, P=0.018). Conclusion(s): We have shown that empagliflozin improved myocardial mitochondrial function and increased energy metabolism, which was accompanied by adequate energy intake and uptake, even in heart failure. Empagliflozin decreased myocardial fibrosis and improved prognosis in failing murine hearts through positive energetical properties including mitochondrial function. The finding that empagliflozin modulates cardiac metabolism in a positive way provides a novel mechanism for the cardioprotective effect of SGLT2 inhibitors in heart failure. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Boehringer Ingelheim